Efficacy of topical Calcipotriol versus combination of topical Calcipotriol plus Betamethasone in the treatment of plaque type psoriasis (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: The effectiveness of various topical agents for the treatment of plaque psoriasis is limited and the results are somewhat not satisfactory to some extent. Topical Calcipotriol can be used either monotherapy or combination therapy with betamethasone. This topical agent has corticosteroid-sparing benefit and reduction of side effects, duration of treatment and also relapse rates when used as combination therapy for the treatment of psoriasis. Objectives: The present study was conducted to compare the clinical efficacy between the topical Calcipotriol and combined formulation of topical Calcipotriol plus Betamethasone in the treatment of plaque type psoriasis. Materials and Methods: A clinical trial was carried out from January 2011 to Jan 2014 in outpatient department of Dermatology and Venereology, combined military hospital- Dhaka and Jessore Cantonment and Bangabandhu sheikh Mujib Medical University, Dhaka. Patients of plaque type psoriasis were the study population. Consequitive type of non-probability sampling method was followed in this study. Patients were divided into two groups.Group A was treated with topical Calcipotriol (0.005%) ointment and group B with combination of topical Calcipotriol plus Betamethasone ointment. Results: The mean percentage of Psoriasis Area and Severity Index (PASI) reduction after 4th week of treatment was 39.4 and 35.4 in group A and group B (p value >0.05) and after 8th week of 74 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 therapy was 59.6 in-group A and 60.7 in-group B respectively. The mean baseline PASI score was 6.7±4.5 and after 8th week it was 2.0 ±1.4 for group A and mean baseline PASI score was 5.5 ±4.2 and after 8th week it was 2.5±1.4 for group B. There was statistically significant reduction in PASI score from base line after 8th week of treatment in both treatment groups (p < 0.001). After 8th week of treatment moderate response was 22(73.3%) in group A and 18(60%) in group B. Very good response was 4 (13.3%) in group A and 8 (26.7%) in group B and minimal response of treatment occurs equally 4 (13.3%) in group A and group B. Conclusion: In the light of the findings of this study, topical Calcipotriol(0.005%) alone or combination with Betamethasone is individually effective for the treatment of plaque psoriasis but combination therapy is more effective than monotherapy. Therefore it may be recommended that monotherapy can be replaced by combination therapy in treating plaque psoriasis. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22929 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014